RANCANGAN PROGRAM LAYANAN BIMBINGAN KLASIKAL BERBASIS KARAKTER DISIPLIN (Studi pada Peserta didik kelas XI IPS 2 dan 3 di MAN 1 Kota Padang) - Septya Suarja (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2020)
This research is motivated by the presence of Guidance and Counseling Teachers who have not been able to compile a classical guidance service program based on student assessment needs. The purpose of this study is to reveal the design of disciplinary character-based guidance services program with the focus of research, namely: 1) Profile of students' disciplinary character, 2) Classification of character guidance services programs in school discipline, 3) The design of classical character-based guidance service programs based on discipline characters. This study uses a mixed-method, for quantitative descriptive research, the population numbered 51 people. The sampling technique uses total sampling. Data analysis techniques using descriptive statistics using the percentage formula. While qualitative research, key research informants were 1 Guidance and Counseling Teacher, and additional informants were 2 people consisting of Guidance and Counseling Teachers, and Homeroom Teacher. The instruments used were interview guidelines and documentation studies, techniques used in data processing through data reduction, data presentation, and drawing conclusions. Based on the results of the study, the following conclusions can be drawn: 1) The profile of the discipline of students' characteristics is generally seen to be in a good category, as well as the written rules in the good category, and the unwritten rules in the good category. 2) Classification guidance service program based on discipline character, one of which is regarding discipline, there are still students who break the rules so it is difficult to change it. Based on the results of the study it can be recommended to students be able to apply disciplinary behavior and obey the rules that exist in the school environment and guidance and counseling teachers provide services based on the character of the discipline.